OSOB NGALAMAN (BAHASA SLANG ASAL MALANG) SEBAGAI SALAH SATU I-CON MALANG (Studi Struktur Osob Ngalaman, dalam Sosial Network) - Aji Setyanto (Jurnal Pariwisata Pesona, 2016)
Malang raya as a place of a tourist destination , must always be innovating and innovation to keep the existence and increase the appeal for tourists. One thing that should not be forgotten is that Malang has Osob Ngalaman or language Malangan. That language has two the main characteristics namely: typical language Malang / the dialect of malang (osob ngalaman) and their language Walikan. Both are fused and inseparable in language usage , both in oral and written. This research is a qualitative descriptive study aims to determine the dialect Malangan covering the structure of words, phrases and grammatical structure of the language used by people in the social network community. These results indicate that the structure of the word in Osob Ngalaman, there are variety of structures, even there is no rule of words between the speakers and the other said flipping the different words. In addition to reverse the order of the letters in the words, in Osob Ngalaman also contained original words such as Genaro, Lawet, Sibun. OsobNgalaman used the words of a language, 2 or even 3 languages (Java, Bahasa, and English). There are sentences that all words are reversed. Generally, not all the words revesed. Number of words that reversed also varies its speakers depends. For the benefit of tourism promotion and sustainability Osob Ngalaman it is necessary to stipulate or established institution OSOB NGALAMAN CENTER. It has a duty major: documenting Osob Ngalaman; conducted a study of continuous to the development of Osob Ngalaman; Formulating simple textbook, making a Osob Ngalaman dictionary; became the central of learning Osob Ngalaman ; designing and planning to using Osob Ngalaman as means of Malang tourism promotion.